2D DIGE proteomic analysis highlights delayed postnatal repression of α‐fetoprotein expression in homocystinuria model mice. Issue 1 (22nd June 2015) - Kamata, Shotaro; Akahoshi, Noriyuki; Ishii, Isao
Abstract : Cystathionine β‐synthase‐deficient ( Cbs −/− ) mice, an animal model for homocystinuria, exhibit hepatic steatosis and juvenile semilethality via as yet unknown mechanisms. The plasma protein profile of Cbs −/− mice was investigated by proteomic analysis using two‐dimensional difference gel electrophoresis and matrix‐assisted laser desorption/ionization‐time of flight/mass spectrometry. We found hyperaccumulation of α‐fetoprotein (AFP) and downregulation of most other plasma proteins. AFP was highly expressed in fetal liver, but its expression declined dramatically via transcriptional repression after birth in both wild‐type and Cbs −/− mice. However, the repression was delayed in Cbs −/− mice, causing high postnatal AFP levels, which may relate to transcriptional repression of most plasma proteins originating from liver and the observed hepatic dysfunction. Abstract : α‐Fetoprotein (AFP) is hyperaccumulated in the plasma and liver of juvenile Cbs −/− mice. Postnatal repression of Afp transcription is delayed in Cbs −/− mouse liver. Expression of other major plasma proteins is downregulated in juvenile Cbs −/− mice. Expression of these plasma proteins is transcriptionally regulated in the liver. High AFP levels may be associated with hepatic steatosis/osteoporosis in Cbs −/− mice.